Are autonomous vehicles the future of mobility? - Drakoulakou, G.; Argyri, P. (Open Schools Journal for Open Science, 2020)
Autonomous vehicles, as well as many other technological inventions, are at the center of attention because of the rapid revolution in the use of new technologies. Autonomous vehicles have been an area of scientific study and research for a very long time. However, the era when driverless cars move in streets is yet to come. That creates the rational question: Are autonomous vehicles really the future of mobility or are they just another viral utopia that will not come true? Most people do not know what exactly that phenomenon is about, thus not understanding the boundaries and hardships of the adaption of such a venture. To figure out what stops driverless vehicles from becoming our reality, we need to examine factors such as what autonomy really is, in what level can and should we achieve autonomy and how will these vehicles exactly operate. That is why it is considered as important to analyze these issues in this paper, as well as the conclusions that emerge as a result of my participation in the European Student Science Parliament, as well as of discussions and interviews with my classmates. After analyzing all the positions, judgments and discussions, the most important problems regarding the adoption of this invention, along with proposing realistic and effective solutions for each of them, are recorded.